Centering Weight Management Clinical Decision Support in Primary Care on Patients With Obesity and Practitioners: A Proof‐Of‐Concept Study - Gudzune, Kimberly A.; Schwartz, Jessica L.; Olsson, Kelly; Almazan, Erik; Beck, Thomas Grader; Ghosh, Jyotsna; Bennett, Wendy L.; Clark, Jeanne M. (Obesity science & practice, 2025)
ABSTRACT Background Clinical decision support systems (CDSS) are electronic health record tools that support practitioners' decision‐making at the point‐of‐care. CDSS may aid clinical care but are not often centered on patients or practitioners. Aims To develop and preliminarily test a CDSS designed to support evidence‐based obesity treatment, promote a patient‐centered experience, and integrate with clinical workflows. Materials & Methods The CDSS allowed patients to complete a pre‐visit questionnaire via the patient portal, which activated multiple elements for the primary care practitioner (PCP). A 3‐month proof‐of‐concept study was conducted among 10 PCPs at 5 clinics to determine usefulness, usability, and acceptability through validated surveys (mean score ≥ 2.5 signified positive outcome; max 5). Using t‐tests, pre‐post differences in PCPs' frequency of self‐reported clinical practices (1‐never; 5‐always) were examined. Results Most PCPs were physicians with mean experience of 10.8 years (SD 7.5). Overall, mean scores for usefulness, usability, and acceptability were 3.2 (SD 0.8), 3.5 (SD 0.9), and 3.6 (SD 0.9), respectively. PCPs reported significant increases in three key clinical practices—counseling on behavioral interventions (3.1 vs. 3.9 [p < 0.01]), referring to weight‐loss programs (2.8 vs. 3.5 [p < 0.01]), and discussing anti‐obesity medications (3.3 vs. 3.8 [p = 0.02]). Conclusion This weight management CDSS was useful and usable for PCPs and improved obesity‐related practice habits. Future studies need to evaluate its impact on patient outcomes.